Corporate Accounting and Accountability for Water in a Chinese Context - Zhu, Hong (Auckland University of Technology, 2025)
Water is one of the most vital natural resources, essential for sustaining ecosystems, human well-being, and economic development. Yet freshwater is exceedingly scarce, with less than 1% of the earth’s water readily accessible for human use. Industrial pollution further strains these limited resources, underscoring the urgency of corporate accountability in water management. Against this backdrop, this thesis investigates water-related information disclosures and corporate water accountability in China. Five research questions guided this study, which related to (1) the extent of water-related disclosure by Chinese companies; (2) motivations for disclosure; (3) stakeholder expectations; (4) whether disclosures meet these expectations; and (5) challenges to corporate water accountability. China provides an ideal context for such an investigation given its global economic role and persistent water issues. A mixed-methods approach was adopted. First, content analysis was used to examine disclosures by 190 listed Chinese companies across their annual reports; corporate social responsibility reports and sustainability reports; and websites. A novel water-specific disclosure index and scoring system were developed to measure the comprehensiveness of the information disclosed. To complement this, 54 semi-structured interviews were subsequently conducted with corporate managers, government officials and policymakers, and a wide range of stakeholders exert influence on corporate actions and disclosures, including shareholders, labour union managers, academics, the media, and an environmental non-governmental organisation (NGO) manager. The findings reveal substantial shortcomings in current water-related disclosures by Chinese companies. Many companies provided only generalised statements lacking quantitative data and detailed explanations. Disclosure quality varied widely, indicating significant room for improvement. The interviews highlighted that stakeholder demands are a key driver of disclosure. Perspectives differed: academics, media representatives and the NGO manager noted a gap between current practices and their expectations, whereas shareholders, regulators, and policymakers generally viewed disclosures as sufficient. Challenges to corporate accountability identified include the absence of standardised reporting frameworks. Without clear guidelines, voluntary disclosures lack consistency, reliability, and credibility. This research contributes to the literature in several ways. First, it analyses the water disclosure practices of 190 Chinese listed companies, filling a gap in corporate water accountability studies. Second, it introduces an innovative water-specific disclosure index, advancing tools for assessing reporting practices. Third, through extensive interviews, it captures diverse stakeholder views, providing nuanced insights into the drivers, expectations, and barriers of corporate water accountability. Practical contributions are equally significant. The proposed index offers Chinese companies a context-specific tool to enhance disclosure comprehensiveness and consistency. It also provides regulators and standard setters with evidence to guide future water reporting policies. By addressing the urgent need for more transparent and reliable water information, this research advances both academic understanding and practical solutions for corporate water accountability in China and beyond.